Advances in multi-photon processes and spectroscopy. - Lin, S. H. (Sheng Hsien), 1937- (Advances in Multi-Photon Processes and Spectroscopy., 1986)
This volume focuses on the recent rapid growth in both experimental and theoretical studies of multiphoton processes and multiphoton spectroscopy of atoms, ions and molecules in chemistry, physics, biology, material sciences, It contains papers readable by active researchers and by those who intend to enter it. Theory and experiment are equally emphasized, and each review article is written in a self-contained manner by experts in the field so that readers learn the subject without much preparation.